DC Electric Drive with Autonomous Power Supply - V. V. Ramanau; R. V. Ramanau (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper examines a circuit of an impulse DC electric drive with one controlled-rectifier that is a thyristor. Regulation of an average voltage value on an engine is carried out by changing frequency of controlling impulses applied to the thyristor. Calculation of commutating capacitance and inductance is given in the paper.